Relationship between physical properties and the magnetic susceptibility in two soils of Valle del Cauca - Jiménez A., Cristian; Benavides B., Jhony; Ospina-Salazar, Daniel I.; Zúñiga E., Orlando; Ochoa B., Oscar; Mosquera G., Carlos (Revista de Ciencias Agrícolas, 2017)
Magnetic susceptibility (MS) is a property that determines the degree of magnetization of a material according to its composition; therefore, it has potential in the assessment of agricultural soils. This study aimed to the application of this attribute to the physical analysis of soils, by determining its correlation with some physical properties in soils of Valle del Cauca. Samples were taken in two lots of sugar cane (Chondular and Santa Rosa), of 55 and 98 hectares, respectively. The lots were analyzed by descriptive statistics and spatial and Pearson correlation between MS and the physical properties of the soil, through a geographic information system software. High spatial correlations were found between MS and the properties analyzed, particularly sand and clay content (0.9 and -0.88, respectively, P<0.001) in Chondular lot, although correlations above 50% were also found with field capacity, thermal conductivity, bulk density and total pore space. Moreover, the correlations of MS were lower in Santa Rosa lot, being the most relevant in the order of 0.59 and -0.65 (P<0.005) also for sand and clay content respectively. These correlation differences were attributed to alterations due to soil tillage in Santa Rosa lot. The determination of MS and its spatial correlation with some physical properties of agricultural soils is a technique that could simplify its characterization, particularly the proportion of sand and clay.